Development and biophysical characterization of a humanized FSH–blocking monoclonal antibody therapeutic formulated at an ultra-high concentration - Satish Rojekar; Anusha R Pallapati; Judit Gimenez-Roig; Funda Korkmaz; Farhath Sultana; Damini Sant; Clement M Haeck; Anne Macdonald; Se-Min Kim; Clifford J Rosen; Orly Barak; Marcia Meseck; et al. (eLife, 2023)
Highly concentrated antibody formulations are oftentimes required for subcutaneous, self-administered biologics. Here, we report the development of a unique formulation for our first-in-class FSH-blocking humanized antibody, MS-Hu6, which we propose to move to the clinic for osteoporosis, obesity, and Alzheimer’s disease. The studies were carried out using our Good Laboratory Practice (GLP) platform, compliant with the Code of Federal Regulations (Title 21, Part 58). We first used protein thermal shift, size exclusion chromatography, and dynamic light scattering to examine MS-Hu6 concentrations between 1 and 100 mg/mL. We found that thermal, monomeric, and colloidal stability of formulated MS-Hu6 was maintained at a concentration of 100 mg/mL. The addition of the antioxidant L-methionine and chelating agent disodium EDTA improved the formulation’s long-term colloidal and thermal stability. Thermal stability was further confirmed by Nano differential scanning calorimetry (DSC). Physiochemical properties of formulated MS-Hu6, including viscosity, turbidity, and clarity, confirmed with acceptable industry standards. That the structural integrity of MS-Hu6 in formulation was maintained was proven through Circular Dichroism (CD) and Fourier Transform Infrared (FTIR) Spectroscopy. Three rapid freeze–thaw cycles at –80 °C/25 °C or –80 °C/37 °C further revealed excellent thermal and colloidal stability. Furthermore, formulated MS-Hu6, particularly its Fab domain, displayed thermal and monomeric storage stability for more than 90 days at 4°C and 25°C. Finally, the unfolding temperature (Tm) for formulated MS-Hu6 increased by >4.80 °C upon binding to recombinant FSH, indicating highly specific ligand binding. Overall, we document the feasibility of developing a stable, manufacturable and transportable MS-Hu6 formulation at a ultra-high concentration at industry standards. The study should become a resource for developing biologic formulations in academic medical centers.